Transformasi Digital: Efisiensi dan Inovasi dalam Manajemen Operasional - Navi Muda Priyatna (Masyarakat Ekonomi Syariah Bogor, 2024)
Operational management is one of the important fields in management science that focuses on managing resources effectively and efficiently to achieve organizational goals. With the increasing development of information and communication technology, it has given birth to digitalization in various sectors. However, to what extent this digital transformation is able to increase efficiency and realize innovation in operational management, an in-depth analysis is needed. The method used in this study is descriptive qualitative, using secondary data analysis. Data collection and literature studies were carried out to determine the right analysis so that it can produce conclusions that are useful for increasing competitiveness and ensuring business continuity. In this study, the adoption of technologies such as AI, IoT, and automation is the key to achieving increased efficiency and opening up opportunities for innovation that have a significant impact on operational management and company performance. Digitalization is the foundation for companies to be competitive and relevant in an increasingly competitive global market. In other words, digital transformation is absolutely necessary, because it is proven that the adoption of digital technologies such as AI, big data, cloud computing, and IoT not only increases the efficiency of operational management, but also paves the way for continuous innovation and rapid adaptation to market changes.